From Peptide Fragments to Whole Protein: Copper(II) Load and Coordination Features of IAPP. Issue 71 (30th November 2017) - Magrì, Antonio; Pietropaolo, Adriana; Tabbì, Giovanni; La Mendola, Diego; Rizzarelli, Enrico
Abstract: The copper‐binding features of rat islet amyloid polypeptide (r‐IAPP) are herein disclosed through the determination of the stability constants and spectroscopic properties of its copper complex species. To mimic the metal binding sites of the human IAPP (h‐IAPP), a soluble, single‐point mutated variant of r‐IAPP, having a histidine residue in place of Arg18, was synthesized, that is, r‐IAPP(1–37; R18H). The peptide IAPP(1–8) was also characterized to have deeper insight into the N‐terminus copper(II)‐binding features of r‐IAPP as well as of its mutated form. A combined experimental (thermodynamic and spectroscopic) and computational approach allowed us to assess the metal loading and the coordination features of the whole IAPP. At physiological pH, the N‐terminal amino group is the Cu 2+ main binding site both of entire r‐IAPP and of its mutated form that mimics h‐IAPP. The histidine residue present in this mutated polypeptide accounts for the second Cu 2+ binding. We can speculate that the copper driven toxicity of h‐IAPP in comparison to that of r‐IAPP can be attributed to the different metal loading and the presence of a second metal anchoring site, the His18, whose role is usually invoked in the process of h‐IAPP aggregation. Abstract : Experimental and theoretical data on Cu‐r‐IAPP (r‐IAPP=rat islet amyloid polypeptide) and mutated Cu‐(r‐IAPP; R18 H) that mimic human amylin showed that i) at physiological pH, both rat and human IAPP (h‐IAPP) coordinate Cu 2+ by NH2 terminal group; ii) histidine‐18 residue accounts for the second Cu 2+ binding in mutated Cu‐(r‐IAPP; R18H). Copper‐driven toxicity of h‐IAPP in comparison to that of r‐IAPP can be attributed to the different metal loading and the presence of a second metal anchoring site: the His18, whose role is usually invoked in the process of h‐IAPP aggregation.